Synthesis, characterizations and hydrophobicity of micro/nano scaled heptadecafluorononanoic acid decorated copper nanoparticle - Chen, Hung-Hsia; Anbarasan, R.; Kuo, Long-Sheng; Tasi, Meng-Yu; Chen, Ping-Hei; Chiang, Kuei-Feng (Nano-Micro Letters, 2010)
Copper nanoparticle was synthesized in the presence of heptadecafluorononanoic acid by the conventional solution immersion method at room temperature from the copper plate, as a resource material. The bulk etching rate was calculated by the weight loss method. The pale green colored Cu-HDFN was characterized by Fourier transform infrared spectroscopy, UV-Visible spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy and contact angle measurements and the results are critically analyzed.